COMPARATIVE ANALYSIS OF THE RESULTS OF USING ARTIFICIAL INTELLIGENCE IN EXPERIMENTAL AND CONTROL GROUPS (Eureka Journal of Education & Learning Technologies, 2026)
This study presents a comparative analysis of the results of using artificial intelligence technologies in experimental and control groups. During the pedagogical experiment, the impact of adaptive tasks, automated assessment, and learning analytics on students’ academic achievement, motivation, independent thinking, classroom activity, and digital competence was examined. The collected data were analyzed using mathematical and statistical methods, including the Student’s t-test. The findings demonstrate a significant improvement in educational quality indicators in the experimental group where AI-based tools were applied, with statistically reliable differences.
Keywords: artificial intelligence, experimental group, control group, education quality, adaptive learning, automated assessment, learning analytics, learning motivation, independent thinking, statistical analysis.